The causal relationship between public spending and economic growth within the framework of Wagner’s law and Keynes’ hypothesis: an applied study on the Libyan economy during the period (1980-2021) (مجلة جامعة سرت للعلوم الانسانية, 2024)
due to the disagreement between Wagner's law and Keynes' hypothesis regarding the direction of the causal relationship between public spending and economic growth, which was reinforced by applied studies in this field, and the nature of this relationship has repercussions on the effectiveness of fiscal policy performance. Therefore, the main objective of this research was to determine the direction of the causal relationship between public spending and economic growth in Libya during the period (1980-2021). In the short and long term, using the Granger methodology and the Toda Yamamoto methodology, respectively. The results of the measurement concluded that there is no causal relationship between the two variables in the short term, and that there is a causal relationship that goes from economic growth to public spending in the long term. Based on the measurement results, the research recommends rationalizing public spending in order to preserve the capabilities of future generations.
Keywords: Wagner’s law; Keynes’ hypothesis; causal relationship; Granger methodology; Toda Yamamoto methodology